Assessing the Impacts of Large Currents and Sedimentation on Coastal Ecosystems - Utama, Lusi; Mizwar, Zuherna; Yulia, Rhani (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Coastal ecosystems are one of the most important and productive ecosystems on our planet. However, coastal ecosystems are also highly vulnerable to environmental changes caused by human activities and natural processes. One of the greatest threats to coastal ecosystems is the impact of large currents and sedimentation. This study aims to assess the impacts of large currents and sedimentation on coastal ecosystems. The study uses both qualitative and quantitative research methods, including field data collection, laboratory analysis, and simulation modeling. The results of the study show that large currents and sedimentation have significant impacts on coastal ecosystems. Large currents can cause coastal erosion, sedimentation, and changes in ecosystem structure. Sedimentation can also lead to decreased water quality, changes in species composition, and disruption of ecological processes. The study also finds that the impacts of large currents and sedimentation on coastal ecosystems can be exacerbated by other factors, such as climate change, human activities, and geological conditions. Therefore, the study recommends that coastal ecosystem management should take into account the impacts of large currents and sedimentation, as well as other factors that can affect coastal ecosystems. The results of this study can be used as a reference for developing sustainable and effective coastal ecosystem management strategies. In addition, the study can also help raise awareness about the importance of coastal ecosystem management and the impacts of large currents and sedimentation on coastal ecosystems